The Effectiveness of The Health Promoting Program Among Makha Elderly Club, Ban Pho Sub-Distric, Mueang District, Nakhon Ratchasima Province - โพธิพิมพ์ มะลิ; เขตบำรุง วลัญช์ชยา; หน่อแก้ว จุน; กุจะพันธ์ จิรวุฒิ (Journal of Health Sciences and Wellness, 2018)
The objective of this research was to study the effectiveness of the health promoting program. It was a quasi-experimental research (one group pretest-posttest design). The samples of the research were randomly selected comprise 70 elders. The research tools were health promoting program, Including; health responsibility, physical activity, nutrition, interpersonal relation, spiritual growth and stress management. Data were collected by interview form. The general data Analysis used descriptive statistics. Comparison mean scores were analyzed by paired sample t-test at 0.05 level of significant. The research findings found that the elderly had a significantly higher mean score of health responsibility, physical activity, nutrition and spiritual growth health promoting behavior than that before the program. On the other hand, the interpersonal relation and stress management health promoting behavior had not difference with before the program. The highest health promoting behavior was stress management and the least practiced aspect was health responsibility. The results of this study suggested that the health promoting behavior program of elderly club had effectiveness in promoting healthy elderly club members. Therefore, such a program should be continuously implemented in other groups of the elderly to maintain their health.